Modern quantum chemistry with [Open]Molcas - Aquilante, Francesco; Autschbach, Jochen; Baiardi, Alberto; Battaglia, Stefano; Borin, Veniamin A.; Chibotaru, Liviu F.; Conti, Irene; De Vico, Luca; Delcey, Mickaël; Fdez. Galván, Ignacio; Ferré, Nicolas; Freitag, Leon; et al. (The Journal of chemical physics, 2020)
MOLCAS/OpenMolcas is an ab initio electronic structure program providing a large set of computational methods from Hartree–Fock and density functional theory to various implementations of multiconfigurational theory. This article provides a comprehensive overview of the main features of the code, specifically reviewing the use of the code in previously reported chemical applications as well as more recent applications including the calculation of magnetic properties from optimized density matrix renormalization group wave functions.